Meningkatkan Keputusan Pembelian melalui Hedonic Shopping Motivation, Shopping Lifestyle, Online Customer Review pada Produk Fashion di Shopee (Studi pada Konsumen Marketplace Shopee) - Muinah Fadhilah; Putri Dwi Cahyani; Dwi Rahmawati (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of Hedonic Shopping Motivation, Shopping Lifestyle, and Online Customer Reviews on Purchasing Decisions. In this study, the population is consumers who have shopped at Shopee e-commerce, using a sampling technique, namely proposive sampling. The instrument test used in this study is the validity test and reliability test. The data analysis technique used in this research is descriptive analysis, classical assumption test, normality test, multicollinearity test, heteroscedasticity test. The analytical test used is linear regression, the hypothesis test used in this study is the t test and F test. The results of this study indicate that: (1) Hedonic Shopping Motivation has a positive effect on purchasing decisions at Shopee, as evidenced by the tcount is 3,045 with a significance level 0.003 <0.05 ; (2) Shopping Lifestyle has no effect on purchasing decisions at Shopee, as evidenced by tcount 1.075 with a significance level of 0.075 > 0.05; (3) Online Customer Reviews have a positive effect on purchasing decisions at Shopee, as evidenced by the tcount is 6.836 with a significance level of 0.000 <0.05; (4) hedonic shopping motivation, shopping lifestyle, and online customer review simultaneously influence the decision to buy fashion products at Shopee, evidenced by the F value obtained is 80.089, it can be concluded that the value of Fcount > Ftable (2.69) with a significant level of 0, 00 < 0.05.